Medieval Origins: A Review Essay on Campbell's The Great Transition - Chaney, Eric (Journal of Economic Literature, 2018)
Bruce M. S. Campbell's The Great Transition: Climate, Disease and Society in the Late-Medieval World is a significant contribution to the growing literature that traces the roots of Europe's economic rise to the climatic and population shocks of the late medieval period. This review essay discusses the empirical, historical, and theoretical support for Campbell's view while highlighting that it struggles to explain why these positive effects were limited to Europe. It then hypothesizes that Europe's differential response to this shock reflected prior institutional advantages and provides some preliminary empirical evidence in support of this hypothesis. The essay concludes by examining Campbell's claim that these shocks contributed to Atlantic Europe's rise prior to the colonial period. ( JEL I15, J11, J13, N13, N33, Q54)